An Analysis of Description of Education Accomplishment and Participation In the Human Development: Research from India: Insights on Education Accomplishment Measurement in India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
These paper breakdowns the measurement issues in educationaccomplishment, and coordination of education objectives and targets, in theconnection of human development in India. Measurement issues are recognized by(a) decision of indicators and variables and (b) data utilized withinestimation/projection/computation of indicators and variables in the globalhuman development reports (HDRS) and in India's national and sub-national HDRS.This analysis establishes the non-likeness of measurement of the educationaccomplishment by indicators and variables, and shows a case for mix ofeducation objectives and targets between global, national and sub-nationallevels. Policy suggestions and goals from these breakdowns of the Indianexperiences offer lessons for measurement of education accomplishment increating countries.